Growth and characterization of epitaxial tin oxide thin films by laser molecular beam epitaxy - Ke, Chang (2012)
The wide variety of electronic, optical and magnetic properties of metal oxides makes them interesting materials for basic research and technological applications. As a well known binary semiconducting oxide, SnO2 based materials combine high electrical conductivity with optical transparency in the visible range of the optical spectrum and thus constitute an important component for optoelectronic applications. These properties are sought in a number of applications, notably as electrode materials in solar cells, light emitting diodes, and flat panel displays. On the other hand, the discovery of room temperture ferromagnetism (RTFM) in 3d transition metals doped SnO2 makes this material more interesting in research and applications, since it combines two important realms of condensed matter physics: magnetism and semiconductor. In this dissertation, the epitaxial growth of SnO2 thin films, electrical transport properties of SnO2 thin films, and the ferromangetism in SnO2:Fe based diluted magnetic semicondctor (DMS) have been systematically investigated.